Kompetensi Sosial Pendidik Dalam Perspektif Al-Quran - Ahmad Zain Sarnoto; Nur Fadhliyah (Ulumuddin: Jurnal Ilmu-ilmu Keislaman, 2022)
This study examines the social competence of educators from the Al-Qur'an perspective, including the affective and psychomotor dimensions based on the values ​​of the Al-Qur'an. This study uses a qualitative approach with data collection techniques through library research and interpretation methods using the maudhu'i interpretation method This research proves that the internalization of Al-Qur'an values ​​in the implementation of educator social competencies will bring out the performance of moral teachers in learning communication according to the example of the Prophet, preventing the appearance of bad traits in students such as hatred, selfishness, unfriendlyness, intolerance. , grudges and other vices that lead to antipathy towards teachers and loss of respect. This research perfects the context of human relations with religious values ​​as a manifestation of faith in Allah, so that from this understanding the theory developed is not only anthropocentric but also theo-anthropocentric.